Data Communication Stability Test a Data Acquisition System (DAQ) for Inpatient Rooms - Sentagi Sesotya Utami; Winny Setyonugroho; Iman Permana; Tri Lestari; Muhammad Dian Saputra Taher; Gilang Ari Widodo; Akhmad Khanif (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
In inpatient services, patient beds are usually limited by curtains or partitions to maintain the patient's safety. At the time of data collection, the barrier or barrier is considered to the effectiveness of the results and validation of medical device sensor data. This study aims to explain the results of the reliability testing of Bluetooth and the internet on hardware and CovWatch applications. This study is action research; comparison is used using devices (tools) with different specifications. Testing internet and Bluetooth connectivity from the CovWatch unit and applications installed on the Samsung A01 devices, Redmi Note 10 and Oppo A57, have mixed results. Hardware CovWatch and Samsung A01 are considered the best in acquiring vital sign data, while Redmi Note 10 and OPPO A57 are not good because some data cannot be obtained so that it does not appear on the monitor unit.